Campur Kode dalam Lirik Lagu-Lagu Bagus Wirata: Kajian Sosiolinguistik - Apriani, Ni Wayan; Aryani, Ni Komang (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
In recent years, the practice of code mixing in public communication in Bali has increased. Code mixing events can occur anytime and anywhere. One form of code mixing that has attracted attention is code mixing in pop song lyrics, especially Balinese pop songs. This is a concern in itself regarding the character of Balinese Pop songs, which were initially aimed at preserving Balinese art and culture, especially in terms of language, but have become something that seems to be forced solely for the sake of market demands. The formulation of the problem in this research is: 1) What is the form of code mixing in the lyrics of songs sung by Bagus Wirata 2) What factors encourage code mixing in the lyrics of songs sung by Bagus Wirata. The research approach used is an empirical method because the use of Balinese in the lyrics of Bagus Wirata's songs already exists naturally. The object of research in this research is the songs sung by singer Bagus Wirata. The data collection methods used were document study, observation and interviews.The research results are; 1. The form of code mixing in the lyrics of songs sung by Bagus Wirata is: The use of code mixing in the form of words is most often used in the lyrics of songs sung by Bagus Wirata with a total usage percentage of 63%. Code mixing in the form of clauses ranks second with a usage percentage of 19%. The remainder is code mixing in the form of phrases amounting to 13%, code mixing in the form of basters 3% and code mixing in the form of repeated words 2%. 2. Factors that encourage code mixing in the lyrics of songs sung by Bagus Wirata are; 1) language dominance, 2) language attitudes, 3) psycholinguistic motivation, 4) lack of equivalent words in Balinese, 5) commercial target market. 3. The impact of using code mixing on the Balinese language, namely; 1) destruction of the Balinese language system, 2) extinction of the Balinese language.